A Poetic Tribute to the Spirit of Canada-Nicaragua Solidarity: Tools for Peace - Hanson, Lori; Walters, Jonah (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2023)
Tools for Peace (T4P) was a grassroots campaign in the 1980s that mobilized Canadians in every province and territory from diverse walks of life and extended large quantities of material support to Nicaragua’s Sandinista revolution. Despite having been recognized by the Nicaraguan state as one of the most important international solidarity efforts of the Sandinista era, T4P has received strikingly little scholarly attention. The paper analyzes 27 interviews with Tools for Peace participants that were conducted in the mid-1980s for an anthology that was never published, the transcripts of which are now found in the public archives at McMaster University. The interviewees’ words evoke the moods, sentiments, and dispositions that animated T4P. Weaving scholar-activism with arts-informed inquiry, this paper presents those sentiments in a series of found poems that seek to both engage and inspire their readers. Through these poems, the paper evokes the experiential and affective dimensions of international solidarity as it was enacted through this novel historical experience. We suggest that T4P was exemplary of the spirit of solidarity in the global movement in support of the Sandinista revolution, but also unique in its Canadian-ness, leading us to advocate a definition of international solidarity that emphasizes its situatedness, together with its experiential and affective dimensions.